Model Pembelajaran CTL Berbasis IT untuk Menguasai Mufradat Bahasa Arab - Adtman A Hasan (Al-Lisan: Jurnal Bahasa, 2019)
The purpose of this study is to; (1) find out how the implementation of contextual teching and learning models based on information technology in Arabic learning, (2) determine whether the contextual teching and learning models based on information technology can improve the mastery of the students’ Arabic vocabulary. The research method used is Classroom Action Research (CAR). The results of this study indicate that the contextual teching and learning models based on information technology in learning Arabic can improve students' Arabic vocabulary mastery in Al-Falah Boarding School, Tunggulo, West Limboto District. This is evidenced by the acquisition of completeness value in cycle 1 reaching 35%. Then in the second cycle there is a 55% increase, so the number of completeness in the second cycle reached 90%.